PSYCHOLOGICAL WORK ENVIRONMENT AS CORRELATE OF TEACHERS’ JOB COMMITMENT IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE - Onwumbiko, Nkechi Agatha (Int'l Journal of Education Research and Scientific Development, 2024)
A positive teaching and learning environment for both students, teachers, and other staff members are essential for promoting academic success and a culture of continuous improvement and mutual respect within educational institutions. The main purpose of this study was to psychological work environment as correlate of teachers’ job commitment in public secondary schools in Anambra State. To achieve this, one research questions guided the study and one null hypotheses were tested at 0.05 level of significance. The study adopted correlational research design. The population of the study comprised 5,133 teachers in 266 public secondary schools in six Education Zones in Anambra State. A sample of 513 teachers (that is, 10% of the population) was used for the study. Multi stage sampling procedure was used for the study. The instruments for data collection were a researcher-structured questionnaire titled: titled “Psychological Work Environment Questionnaire (PWEQ) and Teachers’ Job Commitment Questionnaire (TJCQ). The face validity of the instrument was established by three experts; one from Measurement and Evaluation and two in Education Management. All the experts are all from the Faculty of Education, Nnamdi Azikiwe University, Awka. The reliability was ascertained through a pilot study. The data collected were analyzed with Cronbach Alpha method and coefficient values of 0.83 was obtained. Pearson Product Moment Correlation Coefficient was used to answer the research question and text hypothesis at 0.05 level of significance. The findings of the study showed that psychological work environment positively and significantly correlate with teachers’ job commitment in public secondary schools in Anambra State. The study recommended Public school principals should prioritize efforts to enhance the psychological work environment of public secondary schools, which may include initiatives such as promoting positive staff relationships, implementing support mechanisms for teachers' psychological well-being, and cultivating a culture of appreciation and recognition.